Autologous bone marrow-derived MSCs engineered to express oFVIII-FLAG engraft in adult sheep and produce an effective increase in plasma FVIII levels - Brady Trevisan; Martin Rodriguez; Hailey Medder; Shannon Lankford; Rebecca Combs; John Owen; Anthony Atala; Christopher D. Porada; Graça Almeida-Porada (Frontiers in Immunology, 2022)
IntroductionHemophilia A (HA) is the most common X-linked bleeding disorder, occurring in 1 in 5,000 live male births and affecting >1 million individuals worldwide. Although advances in protein-based HA therapeutics have improved health outcomes, current standard-of-care requires infusion 2-3 times per week for life, and 30% of patients develop inhibitors, significantly increasing morbidity and mortality. There are thus unmet medical needs requiring novel approaches to treat HA.MethodsWe tested, in a highly translational large animal (sheep) model, whether the unique immunological and biological properties of autologous bone marrow (BM)-derived mesenchymal stromal cells (MSCs) could enable them to serve as cellular delivery vehicles to provide long-term expression of FVIII, avoiding the need for frequent infusions.ResultsWe show that autologous BM-MSCs can be isolated, transduced with a lentivector to produce high levels of ovine (o)FVIII, extensively expanded, and transplanted into adult animals safely. The transplanted cells engraft in multiple organs, and they stably produce and secrete sufficient quantities of FVIII to yield elevated plasma FVIII levels for at least 15 weeks.DiscussionThese studies thus highlight the promise of cellular-based gene delivery approaches for treating HA.